2018
DOI: 10.1093/brain/awx384
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a subcortical origin of mirror movements after stroke: a longitudinal study

Abstract: Following a stroke, mirror movements are unintended movements that appear in the non-paretic hand when the paretic hand voluntarily moves. Mirror movements have previously been linked to overactivation of sensorimotor areas in the non-lesioned hemisphere. In this study, we hypothesized that mirror movements might instead have a subcortical origin, and are the by-product of subcortical motor pathways upregulating their contributions to the paretic hand. To test this idea, we first characterized the time course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 40 publications
8
46
0
Order By: Relevance
“…As such, the alpha-band coherence in this study is most likely a release from cortical control, and is consistent with a reticulospinal drive ( 21 ). This view is supported by the findings from a recent longitudinal study ( 41 ).…”
Section: Discussionsupporting
confidence: 67%
“…As such, the alpha-band coherence in this study is most likely a release from cortical control, and is consistent with a reticulospinal drive ( 21 ). This view is supported by the findings from a recent longitudinal study ( 41 ).…”
Section: Discussionsupporting
confidence: 67%
“…The lack of correlation with time since stroke differs from Ejaz et al, who used a longitudinal, as opposed to our study's cross-sectional design. That the CCC AH and fMRI activation maps acquired while patients carried out the same task did not correlate agrees with Ejaz et al (Ejaz et al, 2018), and also with Gerloff et al (Gerloff et al, 2006) who reported significant contralesional M1 overactivation in stroke patients without significant MMs, as determined by EMG coherence. Earlier literature reviews had F o r P e e r R e v i e w already underlined the frequent dissociation between clinically overt MMs and cSM1 overactivations (Calautti et al, 2003).…”
supporting
confidence: 79%
“…In their article, Ejaz et al (Ejaz et al, 2018) interpret the lack of cSM1 overactivation despite MMs, and the observed pattern of MMs with individuated finger presses, as consistent with a brainstem involvement in post-stroke MMs, more specifically the rubrospinal and/or reticulospinal pathways.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, the cerebellum can also influence the inhibitory motor network at the cortical level [105]. On the other hand, it has been suggested that after stroke, mirror movements might be mediated by subcortical instead of cortical networks, suggesting involvement of rubrospinal and reticulospinal pathways [106,107].…”
Section: Discussionmentioning
confidence: 99%